Characterization of some Golfo Dulce drainage basin rivers (Costa Rica) - Umaña V., Gerardo (Revista de Biología Tropical, 1998)
Basic physico-chemical parameters and benthic invertebrate diversity were measured from several streams that drain into the Golfo Dulce (southern Pacific coast of Costa Rica) during 1996-1991. A total of 15 sites were visited in the Osa Peninsula, and the Esquinas and Coto-Colorado river basins, all under 100 m in altitude. Dissolved oxygen and suspended solids differed among sites. even though dissolved oxygen always showed values within a narrow range above 15% saturation, meaning that no site had oxygen deficit at the time of sampling. Suspended solids varied greatly: rivers with high values also had low values during low discharge. A cluster analysis based on the physico-chemical data yielded two groups separated mainly by the variability and maximum value of suspended solids. The benthic fauna is poor in species and is composed of insect larvae (48 species), crustaceans (seven species, of which three are freshwater species) and other three invertebrate species. The most abundant groups were Ephemeroptera and Decapoda. Total diversity was also quite variable (range 1-22 species depending on site). Diversity is best explained by substrate type and suspended solids load.